Unusual heart transplantation for iterative disinsertion of mitral prosthesis. (December 2013) - Pozzi, Matteo; Barreda, Eleodoro; D'Alessandro, Cosimo; Nguyen, Anthony; Leprince, Pascal; Pavie, Alain
Heart transplantation is the gold standard of care for end-stage heart failure, usually associated with an impairment of left ventricular systolic function. We describe a case of heart transplantation in a 58-year-old man with normal left ventricular systolic function, because of recurrent mitral prosthesis disinsertion after multiple reoperations for infective endocarditis.